Status of children's sections of selected city public libraries in District II and District III of Metro Manila with implications towards the development of guidelines for services, staffing and collection development - Aguinaldo, Marjorie E.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2016)
A public library must serve everyone in the community, including the children. To meet the needs of the children, public libraries usually have a children's section which contains various information materials for children. This study sought to determine the current status of the children's section of selected city public libraries in District II and III of Metro Manila and developed a guideline for the services, staffing, and collection development of the children's section based on the perception of library staff responsible for the children's section of the public libraries.
The research instruments used in the study were two unstructured sets of interviews: one aimed to acknowledge the perception of the library staff towards children's sections and one intended to identify the current status of children's section of the public libraries. The library staff-in-charge of the children's sections of the selected city public libraries were interviewed using the two sets of interviews. There were 5 library staff interviewed; 3 from District II and 2 from District III.
The data gathered from the interview from the five library staff reveals that: (a) all of the library staff interviewed handle the children's section but not all of them are library science graduates; (b) the perception of the library staff towards a children's section and the present children's sections of public libraries are not entirely different from each other; (c) the present collection is not yet fully developed since most children's sections only have print materials but also lack non-print resources; (d) the library staff are willing to provide separate rooms for children but it takes a while due to limited financial resources; (e) the libraries have partnerships aside from the local government but it is not enough; (f) most public libraries conduct various services both in and out of the library but most of the children's services conducted are the common ones like storytelling and puppet shows; (g) the library staff are not aware of the facilities and equipment of the children's section are since most of them said that they do not have facilities in the children's section but based on the researcher's observation, they have a few tables, chairs, and shelves; although the children's sections lack equipment that is specifically for children; (h) some library staff in the children's section are not aware of and are not included in the collection development process; and (i) most libraries have limited human resources thus affecting the staffing of the children's sections and necessitates them to request for volunteers.
This study recommends the following: (a) the library especially the children's section should include the 6 collection development process (community analysis, selection policies, selection, acquisition, deselection and evaluation) to build a more appropriate children's collection; (b) not only the local government but also everyone in the community including various groups and organizations should support and continue supporting the library and the children's sections; and (c) future researcher is advised to do a follow up study to know the children better and to know what to improve with the children's sections.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Manila; Children's libraries -- Philippines -- Manila